Hubungan Stres Kerja Perawat Dengan Perilaku Caring Di Rumah Sakit Umum Daerah Muntilan - Putri Sofiatun; Puguh Widiyanto; Sri Hananto Ponco Nugroho (Prosiding University Research Colloquium, 2022)
Background: Nurses are one of the health workers from hospital services andbecome a benchmark in determining the quality of hospital health services. Incarrying out nursing duties, nurses must have a professional attitude startingfrom the physical, psychological, social, and spiritual aspects. Watson's theory ofhuman care reveals that caring is a form of relationship that is needed betweenthe giver and recipient of nursing care, to improve and protect patients, whichwill affect the patient's ability to recover. Caring behavior that is not good willhave an impact on decreasing service quality and client satisfaction, especially inhospitals, besides that it can reduce the number of client visits to health facilitiesand can later cause financial losses to health facilities, where the image of theinstitution is determined by the quality of service which will later be able toincrease client satisfaction and service quality. Objective: to determine therelationship between nurse work stress and caring behavior in MuntilanHospital. Methods: this type of research is descriptive correlation, with a crosssectional approach which data collection uses simple random sampling techniqueand the data is processed using the Spearman test with a sample of nurses in theinpatient room of Muntilan Hospital, totaling 47 nurses. Results: Spearman ranktest results show that there is a significant relationship between nurse workstress and caring behavior with a value (p=0.001 and r=-0.450). Conclusion:There is a relationship between nurse work stress and caring behavior withsufficient correlation strength.